FOLK EXPERIENCE OF FARMING AND GARDENING IN THE KHOREZM OASIS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This study explores the rich folk traditions of farming and gardening in the Khorezm oasis, a historically fertile region in Central Asia. Based on centuries of local knowledge, Khorezmian agricultural practices reflect a deep understanding of irrigation, crop rotation, seed preservation, and sustainable land use. Passed down orally and practically through generations, these customs blend scientific observation with cultural rituals. The paper examines how folk farming systems adapted to ecological challenges and continue to influence modern agriculture, despite external influences and technological shifts.